Dynamic Motion of Ru‐Polyoxometalate Ions (POMs) on Functionalized Few‐Layer Graphene. Issue 23 (1st July 2013) - Ke, Xiaoxing; Turner, Stuart; Quintana, Mildred; Hadad, Caroline; Montellano‐López, Alejandro; Carraro, Mauro; Sartorel, Andrea; Bonchio, Marcella; Prato, Maurizio; Bittencourt, Carla; Van Tendeloo, Gustaaf
<x xml:space="preserve">Abstract</x> The interaction and stability of Ru4POM on few layer graphene via functional groups is investigated by time‐dependent imaging using aberration‐corrected transmission electron microscopy. The Ru4POM demonstrates dynamic motion on the graphene surface with its frequency and amplitude of rotation related to the nature of the functional group used. The stability of the Ru4POM–graphene hybrid corroborates its long‐term robustness when applied to multielectronic catalytic processes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>